By issue of planning in tourism (Journal of Geography and Environmental Management, 2018)
The point of tourism development planning consists in a continuousprocess of designing plans; a conformity of the established aims and objectivesin the tourism industry; and an identification of methods and instrumentsin achieving those aims and objectives. It is important that a singleinstitute manages the tourism industry of a country (e.g. Ministry of Tourism),as it would effectively coordinate the performances of regional tourismorganizations. Problems in the tourism development of the Republic ofKazakhstan are being solved inefficiently. In order to enhance the qualityof tourism services, it is extremely important to develop a certification processin the tourism sector. During the education process, the universitiesof the Republic of Kazakhstan, which produce specialists for the tourismindustry, should practicean active cooperation with the real sector. Thiswill allow the universities to train professional and competitive managersfrom the first year of education.